Is it time to consider quaternary injury prevention in sports? - Brito, J.; Mendes, R.; Figueiredo, P.; Marques, J. P.; Beckert, P.; Verhagen, E. (Sports Medicine, 2023)
Prevention has traditionally been categorized into three main areas: primary, secondary, and tertiary. In this Current Opinion, we present and discuss the concept of quaternary prevention in sports. Quaternary prevention aims to protect individuals from interventions that likely cause more harm than good, such as overdiagnosis, overtreatment, and overmedication. It includes preventing all types of harm associated with training and clinical interventions. Therefore, any sports injury prevention model or strategy should acknowledge the risks associated with training-related (i.e., overreaching and overuse) and clinical-related (i.e., overdiagnosis, over medicalization, and overtreatment) features. We propose a conceptual framework that integrates quaternary prevention into the contemporary injury prevention models in sports, taking into account that injury prevention is just one branch of the managerial, decision-making, and active hazard control process of risk management that athletes, coaches, and health and performance staff need to deal with. Therefore, we argue that integrating the concept of quaternary prevention into any form of prevention will significantly protect athletes from excessive, inappropriate, and ethically questionable interventions that may likely cause more harm than good.